Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/chin.200221013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Novel Concept for the Synthesis of an Improved LiFePO4 Lithium Battery Cathode.

Abstract: A Novel Concept for the Synthesis of an Improved LiFePO 4 Lithium Battery Cathode.-A kinetically improved LiFePO 4 cathode material is prepared by a sol-gel route involving the dispersion of Cu or Ag at a very low concentration (1 wt%). The metal dispersion does not affect the structure of the electrode material but substantially enhances its overall capacity. -(CROCE, F.; D' EPIFANIO, A.; HASSOUN, J.; DEPTULA, A.; OLCZAC, T.; SCROSATI, B.; Electrochem. Solid-State Lett. 5 (2002) 3, A47-A50; Dip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…In the battery type comparison, LFP shows the longest cycle life. Other studies [34], [60] have also shown that LFP cells have longer cycle life compared to other types of lithium-ion batteries. Yet this result does not lead to the conclusion that LFP cells are the best choice for frequency regulation because battery types also differ in efficiency, energy density, and production cost.…”
Section: Model Application Case Studymentioning
confidence: 93%
“…In the battery type comparison, LFP shows the longest cycle life. Other studies [34], [60] have also shown that LFP cells have longer cycle life compared to other types of lithium-ion batteries. Yet this result does not lead to the conclusion that LFP cells are the best choice for frequency regulation because battery types also differ in efficiency, energy density, and production cost.…”
Section: Model Application Case Studymentioning
confidence: 93%
“…The materials demonstrate exceptional stability and can provide high voltage and capacity when used in lithium based batteries, but their characteristically low electrical conductivities1014 are their biggest challenge for implementation as battery materials. In order to enhance Li x MPO 4 electrical conductivity, several strategies have emerged in the scientific literature, including coating of Li x MPO 4 particles with carbon, 15, 16 co-synthesizing the Li x MPO 4 materials with carbon to achieve intimate contact of the particles with the conductive material,13, 17 adding silver and copper powder to the Li x MPO 4 matrix to achieve improved conductivity,18, 19 or the solid-solution doping of LiFePO 4 20. Unfortunately, the strategies involving the addition of an external conducting material require additional processing steps and can significantly reduce energy density due to the presence of the extraneous inert conducting material.…”
Section: Introductionmentioning
confidence: 99%
“…There were systematic works of many research groups worldwide to adopt various processes and methods to overcome the main disadvantage of LiFePO 4 restricting its application, low electronic conductivity. Various methods have been applied, including different synthesis techniques, coating by a conductive layer of carbon [3][4][5][6] and dispersed metal particles [7], preparation of LiFePO 4 /carbon composites [5,[8][9][10][11], producing smaller particles of cathode material [5,7,12]. Nowadays, LiFePO 4 cathode has become one of the main commercial cathode materials for lithium batteries.…”
Section: Introductionmentioning
confidence: 99%